Gas infiltration of bromine to enhance the electrical conductivity of carbon nanotube fibers. (5th December 2018) - Wang, Ping; Liu, Dandan; Zou, Jingyun; Ye, Yuanhang; Hou, Ligan; Zhao, Jingna; Men, Chuanling; Zhang, Xiaohua; Li, Qingwen
Abstract: Highly conducting and lightweight wires can be created based on carbon nanotube (CNT) assembly materials, where the inter-tube electron transport plays a key role. Here we report a gas infiltration of bromine to improve the electrical properties of CNT fibers, owing to the enhanced inter-tube electron hopping. Although Br infiltration is mainly a physical absorption process, with just a little fraction to form covalent bonding with the defect of CNTs, it can induce electron transfer from CNT to Br. Together with the densification effect, there are more pathways for interfacial electron transport between the CNTs. As a result, the infiltration efficiently increases the electrical conductivity from 2.66 × 10 5 to 1.63 × 10 6  S/m, by 6-fold. Based on the high performance stability, the composite fiber can be used as lightweight and functional conductor for wearable smart devices. Graphical Abstract: Highlights: Bromine infiltration increases the electrical conductivity of carbon nanotube fiber. Interfacial electron transfer from carbon to bromine makes carbon nanotubes p-doped. Bromine-infiltrated carbon nanotube fiber can be used as a functional wire.